Workshop Penyusunan Pedoman Penilaian Pembelajaran Program Studi Teknologi Laboratorium Medis Poltekes Tanjung Karang - Nina Kadaritna; Undang Rosidin; Widyastuti; Handoko (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2023)
This community service activity aims to produce learning assessment guide products that describe the increased knowledge and skills of the lecturers of the Medical Laboratory Technology Study Program. This activity is carried out in the form of a workshop that combines lecturing, simulation, and evaluation strategies. The activity, which was carried out on 20-22th December 2022 in the Hall Room of the Tanjungkarang Polytechnic Medical Laboratory Technology Department, involved 15 active participants. The results of the activity showed that the participants experienced an increase in knowledge and skills with an average gain score 0.40 out of 1.00 (medium category) and the Learning Assessment Guideline product produced by the participants illustrates the increase in the quality of knowledge and skills acquired by the participants.